The Plant-Specific Dof Transcription Factors Family: New Players Involved in Vascular System Development and Functioning in Arabidopsis - Le Hir, Rozenn; Bellini, Catherine (Frontiers in Plant Science, 2013)
In higher plants phloem and xylem are responsible for long-distance transport of water, nutrients, and signals that act systemically at short or long distance to coordinate developmental processes. The formation of the plant vascular system is a complex process that integrates signalling events and gene regulation at transcriptional and posttranscriptional levels. Thanks to transcriptomic and proteomic analysis we start to better understand the mechanisms underlying the formation and the functioning of the vascular system. The role of the DNA-binding with one finger (Dof TFs), a group of plant–specific transcription factors, recently emerged as part of the transcriptional regulatory networks acting on the formation and functioning of the vascular tissues. More than half of the members of this TF family are expressed in the vascular system. In addition some of them have been proposed to be mobile proteins, suggesting a possible role in the control of short- or long-distance signalling as well. This review summarizes the current knowledge on Dof TFs family in Arabidopsis with a special focus on their role in vascular development and functioning.